Motorcycle wheel rim press tool design - I Nengah Ludra Antara; I Nyoman Sutarna; Ida Bagus Puspa Indra; I Nyoman Gunung (Journal of Applied Mechanical Engineering and Green Technology, 2022)
In motor vehicles, especially motorcycles, sometimes there are a lot of problems with the wheel rim in the event of an accident, or hit by a pothole that causes the wheel rim to be dented. In this case, we design a motorcycle wheel rim press tool as shown in Figure 2.1. The things that must be considered for a tool design in material selection are hardness, strength, fragility. The types of materials used are carbon steel, alloy steel, hollow steel, U iron, axle iron, angle iron, plate iron. In general, there are several grades of iron, including JIS G3101 SS400, ASTMA 36; BS 4360; DIN 17 100JIS G 3101; JIS 3106; SNI 07 2054, which has a different maximum tensile strength or stress by using formulas, for example the calculation of shafts, levers, weld strength and selection of hydraulic jacks. Supporting instruments in the process of working on the wheel rim press tool are machine tools and other measuring tools. To obtain truly satisfactory results from a tool, we are required to observe and look for alternatives and as carefully as possible in order to achieve a result that meets the standard. The tool must have high efficiency, easy to operate, and uphold work safety. Based on the results of the design and testing of the design of this motorcycle wheel rim press tool, it is more efficient, fast, and precise when compared to the tools owned by David Jaya Motor's workshop. The time required is faster according to the test results, which is between 25 minutes to 40 minutes with different wheel rim damage cases, while manually at the David Jaya Motor workshop, from observing field test results it takes a minimum of 90 minutes.